The Degree of Need for Counseling Services for Families with Disabilities in Kuwait City From The Point of View of Mothers - Sharika, Falah hammoud Hussein (Technium Social Sciences Journal, 2022)
The study aimed to measure the degree of need for counseling services for families with disabilities in Kuwait City from the mothers' point of view, and to measure the statistically significant differences at the significance level (α 0.05 ≥ ) in the average degree of need for counseling services for mothers with disabilities in Kuwait attributed to (type of disability, level of mother’s education) and relied on the descriptive correlative approach, and the study community consisted of mothers of individuals with needs in Kuwait City, and the size of the study community of mothers in the two cities for children in rehabilitation centers for the disabled is about (220) mother . The study showed a high degree of need for counseling services for families of people with disabilities, and the presence of statistically significant differences in the degree of cognitive needs and the degree of need for social support due to the difference in the type of disability, and the absence of differences in the degree of counseling needs due to the difference in the level of mother’s education, in light of The results of the study recommend conducting more studies related to the counseling needs of families with special needs in Kuwait, and studying the reasons for the poor availability of psychological counseling services needed by mothers.